Endolysosomal compartments as platforms for orchestrating innate immune and metabolic sensors. Issue 4 (20th June 2019) - Miyake, Kensuke; Saitoh, Shin-ichiroh; Sato, Ryota; Shibata, Takuma; Fukui, Ryutaro; Murakami, Yusuke
Abstract: TLRs respond to a variety of microbial products and initiate defense responses against bacteria and viruses. A variety of pathogens invade into and control the endosomal compartment to survive in host cells. On the other hand, host cells deploy cell surface and endosomal TLRs to pathogen-containing vesicles to mount defense responses. The endosomal compartment is a site for pathogen-sensing. As TLR-dependent defense responses are accompanied with a shift to the anabolic state, TLR responses need to be under metabolic control. Cellular metabolic state is monitored by sensing lysosomal metabolites by the mammalian target of rapamycin complex 1 (mTORC1). Type I IFN production induced by endosomal TLRs requires mTORC1. Recent studies have demonstrated that the interaction between TLRs and mTORC1 depends on their anterograde movement to the cell periphery. In a nutrient-sufficient state, a molecular complex called Ragulator recruits and activates mTORC1 in lysosomes. In parallel, Ragulator allows the small GTPase Arl8b to drive lysosomes to the cell periphery. Nutrient-activated mTORC1 in peripheral lysosomes is constitutively associated with type I IFN signaling molecules such as TRAF3 and IKKα. On the other hand, TLR7 and TLR3 are activated in the endosomal compartment and induce trafficking of TLR-containing vesicles to the cell periphery in a manner dependent on Arl8b or another GTPase Rab7a, respectively. Lysosomal trafficking helps TLR7 and TLR3 to interact with nutrient-activated mTORC1 and type I IFN signaling molecules. The endosomal compartments serve as platforms where metabolic sensing machinery licenses TLRs to initiate type I IFN responses. Graphical Abstract: Review on how endosomal compartment actively controls interaction between TLRs and metabolic sensors.